Endometriosis: Sonographic spectrum - Bhatt, Shweta; Kocakoc, Ercan; Dogra, Vikram S. (My University, 2006)
Endometriosis is the presence of functional endometrial tissue outside the uterine cavity and the myometrium. It is an important cause of infertility and pelvic pain in women older than 25 years. Endometriomas are relatively common and can mimic other adnexal masses, and ultrasonography is often the first choice of imaging. This pictorial essay presents the sonographic appearance of endometriomas and similar-appearing adnexal masses and their characteristics, which may aid in their differentiation on routine ultrasonographic examination. © 2006 Lippincott Williams & Wilkins, Inc.
Keywords: Endometriosis; Endometriosis/ultrasonography/extraovarian; Hemorrhagic cyst; Mature cystic teratoma